The microplasma aluminum and titanium oxidation in condensed environments - Vinnikov, D.V.; Ozerov, A.N.; Yuferov, V.B.; Fomin, V.T. (Вопросы атомной науки и техники, 2020)
The plant intended for the microplasma oxidation of the materials whose oxides possess semiconductor properties has been developed. The coatings consisting of corundum Al²O³-α (hexagonal syngony) and the two transition modifications of aluminum oxide Al²O³-η (cubic syngony) and Al²O³-θ (monoclinic syngony) were cultivated by the aluminum substrate. The crystals in the form of anatase and rutile oxides (tetragonal syngony) were grown by the titanium substrate. The Al hardness was increased from 81 tо 97 as for the HRB scale. The adhesion force for the aluminum substrate ranged from HF1 to HF3, and for the titanium substrate it was HF3. The coating morphology was established. The coatings were applied on aluminum items. The promising fields of application were defined. Створена установка для здійснення процесу мікроплазмового оксидування матеріалів, оксиди яких мають напівпровідникові властивості. Отримано покриття на алюмінії, що складаються з корунду Al²O³-α (гексагональна сингонія) і двох перехідних модифікацій оксиду алюмінію: Al²O³-η (кубічна сингонія) і Al²O³-θ (моноклінна сингонія). На титані отримані кристали у вигляді оксидів анатазу і рутилу (тетрагональна сингонія). Для Al твердість за шкалою HRB зросла з 81 до 97. Сила адгезії для алюмінію - HF1...HF3, для титану - HF3. Отримана морфологія покриттів. Проведено нанесення покриттів на алюмінієві вироби. Позначені подальші застосування. Создана установка для осуществления процесса микроплазменного оксидирования материалов, оксиды которых обладают полупроводниковыми свойствами. Получены покрытия на алюминии, состоящие из корунда Al²O³-α (гексагональная сингония) и двух переходных модификаций оксида алюминия: Al²O³-η (кубическая сингония) и Al²O³-θ (моноклинная сингония). На титане получены кристаллы в виде оксидов анатаза и рутила (тетрагональная сингония). Для Al твердость по шкале HRB выросла с 81 до 97. Сила адгезии для алюминия - HF1...HF3, для титана - HF3. Получена морфология покрытий. Проведено нанесение покрытий на алюминиевые изделия. Обозначены дальнейшие применения.